2022
DOI: 10.1111/jeu.12949
|View full text |Cite
|
Sign up to set email alerts
|

Further insight into the genetic diversity of Entamoeba coli and Entamoeba hartmanni

Abstract: Despite the species' wide distribution, studies of the genetic diversity within Entamoeba coli and Entamoeba hartmanni remain limited. In the present study, we provide further insight into the genetic diversity of both species based on analysis of partial nuclear small subunit ribosomal DNA sequences generated from human faecal DNAs from samples collected in Africa, South America and Europe. Reinforcing the previous recognition that E. coli is a species complex, our data confirm the existence of the two subtyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…This study reports the infection of E. hartmanni in wild Tibetan macaques for the rst time. In previous research, Stensvold et al proposed there were three subtypes of E. hartmanni (Stensvold et al, 2023). Based on the nucleotide similarity between the sequences of E. hartmanni obtained from the present study and E. hartmanni ST2 (FR686377), as well as the topology of the phylogenetic tree, we suggest E. hartmanni may have a novel subtype named ST4.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…This study reports the infection of E. hartmanni in wild Tibetan macaques for the rst time. In previous research, Stensvold et al proposed there were three subtypes of E. hartmanni (Stensvold et al, 2023). Based on the nucleotide similarity between the sequences of E. hartmanni obtained from the present study and E. hartmanni ST2 (FR686377), as well as the topology of the phylogenetic tree, we suggest E. hartmanni may have a novel subtype named ST4.…”
Section: Discussionsupporting
confidence: 67%
“…Meanwhile, genetic analysis based on the tRNA-linked short tandem repeat (STR) loci showed E. nuttalli has genotypic polymorphisms (Feng et Mon et al, 2021). In addition, based on the small-subunit ribosomal RNA (SSU rRNA), three subtypes of E. hartmanni (ST1, ST2, and ST3) were reported (Stensvold et al, 2023). In summary, studies in NHPs have shown that Entamoeba may have high genetic diversity, and genotyping of potentially pathogenic species such as E. nuttalli will provide basic data for studying its genetic diversity.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in suids and NHPs, we identified the uninucleated cysts as E. polecki -like [ 66 ]. The eight-nucleated cysts found in NHPs would correspond to Entamoeba coli , but since it is actually considered a species complex [ 75 ], it would be best to identify the findings as E. coli -like. In general, the E. bovis -like, E. polecki -like, and E. coli -like species are considered non-pathogenic, although [ 76 ] reported a case of symptomatic infection in humans by E. polecki , [ 77 ] suggested an association between the presence of E. bovis and diarrhoea in cattle, and Coke et al [ 78 ] reported a fatal case in which unidentified Entamoeba and Acanthamoeba Volkonsky 1931 were found in gastric ulcers in an 11-month-old female giant anteater.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of ST3, we propose a new subtype rather than a distinct species, since sequence identities of 95% between ST1 and ST3 are clearly higher than between ST1 and ST2 with 88 to 89% identity in the 18S rRNA gene. Additionally, for Entamoeba coli , a third subtype has been proposed just recently with 7% and 13% sequence dissimilarity to previously defined sequence types, but is only based on just a 484 bp portion of the 18S gene [ 36 ]. In the current study, the entire 18S rRNA gene was used for phylogenetic analyses.…”
Section: Discussionmentioning
confidence: 99%